PREPUBERTAL GYNECOMASTIA: A RARE MANIFESTATION OF MYOTONIC DYSTROPHY TYPE 1 - Miranda,Patrícia Sofia Ferreira (2020)
ABSTRACT Objective: To present a case of bilateral gynecomastia in a prepubertal boy with autism spectrum disorder, diagnosed with myotonic dystrophy type 1. Case description: A 12-year-old boy with autism spectrum disorder presented at a follow-up visit with bilateral breast growth. There was a family history of gynecomastia, cataracts at a young age, puberty delay, and myotonic dystrophy type 1. The physical examination showed that he had bilateral gynecomastia with external genitalia Tanner stage 1. Neurologic examination was regular, without demonstrable myotonia. The analytical study revealed increased estradiol levels and estradiol/testosterone ratio. After excluding endocrine diseases, the molecular study of the dystrophia myotonica protein kinase gene confirmed the diagnosis of myotonic dystrophy type 1. Comments: A diagnosis of prepubertal gynecomastia should include an investigation for possible underlying diseases. This case report highlights the importance of considering the diagnosis of myotonic dystrophy type 1 in the presence of endocrine and neurodevelopmental manifestations.